Efektifitas Pemberian Kompos Trichoderma Sp. Terhadap Pertumbuhan Tanaman Cabai (Capsicum Annum L.) - SETYADI, I MADE DEDIK; ARTHA, I NENGAH; WIRYA, GUSTI NGURAH ALIT SUSANTA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.6, No.1, Januari 2017, 2017)
Effectiveness composting Trichoderma sp. Against the Plant Growth Chilli (Capsicum annum L.) The objective of this study was to determine the effectiveness of compost Trichoderma sp. at the time of the nursery and moving the field on red pepper plants. This experiment was conducted February to April 2015, using a factorial randomized complete block design with three replications. The first factor seedling media (MT = Media soil + compost Trichoderma sp. With a volume ratio of 1: 1, MK = Media soil + compost Simantri the ratio of 1: 1, M = Media ground). The second factor in the media field (mt = Media soil + compost Trichoderma sp. With a volume ratio of 1: 1, mk = Media soil + compost Simantri the ratio of 1: 1, m = Media ground). The results showed that: there is interaction between media seedlings with the media on the field, the variables plant height and yield fruit of pepper plants in the field. The best treatment is shown by the media's treatment (MTmk) at high variable pepper is 61.67 cm and the media (MTmt) high were obtained are 60.78 cm. In the fruit of the pepper plant variables highest results in treatment (MTmt) with the amount of 916.67 g but not significantly different from the treatment (MKmt) with the results of 813.33 g.
Keywords: Effectiveness, Trichoderma sp, chili plants